Back pain and functional status in patients with ankylosing spondylitis during pregnancy - O. A. Krichevskaya; Z. M. Gandaloeva; A. B. Demina; S. I. Glukhova; T. V. Dubinina (Современная ревматология, 2019)
Inflammatory rhythm back pain and enthesitis are one of the main clinical manifestations of ankylosing spondylitis (AS), which increase in severity during pregnancy. However, addition of back pain and, possibly, enthesis in the second half of gestation, which is associated with normal pregnancy, needs to make a differential diagnosis for clarifying the genesis of pain and choosing the right management tactics, which determines the relevance of this study.Objective: to investigate the course of pain in the back, enthesis, and inguinal region, as well as the functional status in AS patients during pregnancy and to reveal clinical signs that most accurately reflect inflammatory activity during gestation.Patients and methods. A study included 36 pregnant women with a reliable diagnosis of AS according to the modified New York criteria (1984). Their mean age was 31.6±4.8 years, the mean age at the onset of AS was 21.8±10.9 years; the duration of the disease was 134.9±89.3 months. A control group comprised 30 healthy pregnant women with no history of back pain and arthritis; their mean age was 28.2±4.5 years. The pregnant women of both groups were matched for parity. They made visits at 10–11, 20–21, and 31–32 weeks of pregnancy. Pain intensity was estimated using the numerical pain rating scale (NPRS) and the functional status was assessed by the Bath Ankylosing Spondylitis Functional Index (BASFI). The Maastricht Ankylosing Spondylitis Enthesitis Score (MASES) was used to assess enthesitis.Results and discussion. During pregnancy, 94% of AS patients had back pain; its intensity by trimesters was 3 [2; 4], 4 [3; 5.5], 3 [2; 7] and was higher than in healthy pregnant women (p<0.0001). In the study group, there was a rise in pain intensity at night with increasing gestational age (n=23–28): 2 [1; 4] in the first trimester; 3 [0; 5] II in the second trimester; 3 [1; 6] in the third trimester (p< when comparing the first, second, and third trimesters) and an increase in the duration of morning stiffness (n= ): 10 [5; 20], 15 [10; 55], and 15 [5; 60] min, respectively. Moreover, the number of women who reported improvements after exercise (85–63%) and no improvement at rest (88–56%) declined (p<0.05 when comparing the first, second, and third trimesters).In the control group, 1 and 3 patients had morning back stiffness and night pain, respectively. The healthy pregnant women more frequently reported a reduction in back pain after exercise in the third trimester (66.7% of those with pain) than in the first trimester (20% of those with pain) (p<0.05).By the third trimester, the patients with AS showed a change in the nature of back pain: 43.7% of the patients reported an improvement at rest; 42.4% noted an increase in pain after exercise, while the frequency of elements of mechanical back pain was less than that in the control group (p < 0.05).The intensity of groin pain (2.4±1.9, 3.3±2.4, and 4.3±3.0 in the first, second, and third trimesters, respectively) did not differ in AS patients with and without coxitis or pelvic enthesitis. The frequency of enthesitis and MASES scores in the study group were higher than in the control group (p<0.05), the MASES scores increased with gestational age, amounting to 0 [0; 1] in the first trimester and 2 [0; 3] in the third trimester (p<0.05).Functional disorders during pregnancy increased in both groups; there was a difference in BASFI scores between the groups only in the third trimester: 3.5±2.8 and 1.7±1.2, respectively (p<0.05).Conclusion. Back pain and functional disorders increase in AS patients during gestation. Night back pain, morning stiffness, and enthesitis reflect the inflammatory activity of AS during pregnancy. Mechanical back pain joins in 40% of women with AS in the third trimester. The criteria for inflammatory back pain and BASFI require adaptation when used in pregnant women.